ChemInform Abstract: One‐Pot Oxidation/Isomerization of Z‐Allylic Alcohols with Oxygen as Stoichiometric Oxidant. Issue 10 (7th March 2013) - Koenning, Daniel; Hiller, Wolf; Christmann, Mathias
Abstract Treatment of (Z)‐allylic alcohols with oxygen, CuOTf, TEMPO, the bipyridine (MOP), and DMAP or azajulolidine allows an efficient and selective access to (E)‐α, β‐unsaturated aldehydes.